KEPEMIMPINAN LURAH DALAM MENJALANKAN TUGAS POKOK DAN FUNGSI DI KELURAHAN KADIDI KECAMATAN PANCARIJANG KABUPATEN SIDENRENG RAPPANG - Edy Muhtar (PRAJA: Jurnal Ilmiah Pemerintahan, 2018)
The research was carried out in the kelurahan kadidi with the aim of knowing the leadership of the lurah in carrying out his main duties and functions and what factors influence the leadership of the lurah. Data research techniques used are surveys, questionnaires and interviews. The population is 50 people, and the total sample is 50 people. The data analysis technique used is quantitative. The results of this study indicate that the leadership of the lurah in carrying out his main duties and functions, at the level of carrying out the main tasks of the lurah, for example in development affairs in the form of maintaining urban village road facilities with a percentage of 74% is classified as good. 76% is classified as good. as well as social affairs in the form of spiritual (religious) development with a percentage of 82% classified as good, Meanwhile in terms of the implementation of the function of the Lurah, there are several functions that are still not well carried out by the Lurah, namely in terms of community empowerment in the form of posyandu development, with a percentage of 22% classified as not good . and family planning, with a percentage of 58% classified as poor. and maintenance of infrastructure and public service facilities in the form of irrigation development, with a percentage of 76% still classified as poor. This is expected to provide benefits for the Government, especially in Kadidi Village, Pancarijang District, Sidenreng Rappang Regency. So that the results of this study can be used as input or consideration in terms of implementing the main tasks and functions of the lurah in the future in the Kadidi Village, Pancarijang District, Sidenreng Rappang Regency.